Hurricane Lamps and Childhood Memories in Printmaking Artworks - Putra, Abdi Bela; Rajudin, Rajudin; Nazaruddin, Armen (Institut Seni Indonesia Padang Panjang, 2024)
This creation is inspired by a hurricane lantern as the object of creation. The hurricane lantern is chosen as the object because it is one of the items that can remind me of my childhood memories with my father. These memories are from the nights spent in the fields peeling cinnamon bark (cassia vera). The purpose of creating this artwork is to express feelings of longing and affection for my father in the form of black-and-white relief print printmaking. The method used involves several stages: preparation, design, forming, and presentation. This creative process resulted in five black-and-white relief print printmakings, titled